PENGARUH LATIHAN PLYOMETRIK TERHADAP KECEPATAN TENDANGAN SABIT ATLET PERGURUAN PENCAK SILAT ELANG PUTIH - Husna; Desi Purnama Sari; Alnedral; Jeki Haryanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of plyometric training on the speed of sickle kicks of athletes from the Elang Putih Pencak Silat School. The low speed of sickle kicks makes athletes' movements easier to anticipate by opponents during matches. This study used an experimental method with a one-group pretest-posttest design. The study population was 40 athletes, while a sample of 20 athletes was determined using a purposive sampling technique. The research instrument was a 10-second sickle kick speed test. The treatment given was plyometric training throughout the study period. Data analysis was carried out using the Shapiro–Wilk normality test and a paired sample t-test at a significance level of 0.05. The results showed an increase in sickle kick speed after being given plyometric training. The average pretest result was 19.45, increasing to 30.65 in the posttest. The results of the analysis obtained a calculated t of (25.805) > t table (2.093) at a significance level of 0.005. Thus, it can be concluded that plyometric training has a significant effect on increasing the speed of the sickle kick of athletes at the Elang Putih Pencak Silat School. Keywords: plyometric training, sickle kick speed, sickle kick, pencak silat athletes, pencak silat.